A large-scale deep-blue tetraphenylbenzene-bridged hybridized local and charge transfer fluorophore exhibiting small efficiency roll-off and low amplified spontaneous emission threshold. (5th July 2022) - Ying, Shian; Lv, Jichen; Li, Yuanzhao; Huo, Yumiao; Liu, Yuchao; Ma, Dongge; Peng, Ling; Yan, Shouke
Abstract : A deep-blue HLCT emitter PTPC achieved a high EQE of 6.78% in a non-doped OLED as well as a low ASE threshold of 1.18 μJ cm −2 . Abstract : Efficient and stable deep-blue organic luminescent materials are important but rare for application in full-color displays due to their intrinsic wide bandgap characteristics. Here, a high-performance deep-blue hybridized local and charge transfer fluorophore PTPC with the aggregation enhanced emission (AEE) effect has been designed and synthesized with 1, 2, 4, 5-tetraphenylbenzene as the bridge. High morphological stability, high photoluminescence efficiency, fast radiative rate, suitable energy levels, and bipolar-transporting properties are obtained simultaneously by incorporating a twisted molecular skeleton with weak, rigid and nearly flat donor/acceptor groups. As a result, a high forward-viewing external quantum efficiency of 6.78% as well as a deep-blue emission with the Commission Internationale de l'Eclairage coordinates of (0.156, 0.059) is achieved in a non-doped organic light-emitting diode (OLED). The EQEs still remain as high as 6.73% and 6.18% at 100 and 1000 cd m −2, showing a small efficiency roll-off. Furthermore, PTPC exhibits extraordinary amplified spontaneous emissions (ASEs) with a low threshold of 1.18 μJ cm −2 and a gain coefficient of 36.6 cm −1 . This work provides a new insight into creating high-performance deep-blue organic semiconductors with marked ASE performance for further practical applications.